Miasta rzymskie nad dolnym Dunajem w okresie przełomu (III–IV w.) ze szczególnym uwzględnieniem miasta Novae - Mrozewicz, Leszek (Studia Europaea Gnesnensia, 2010)
The article treats of the development of Roman cities on the Lower Danube, in the provinces of Upper and Lower Moesia. All these settlements were created in the vicin-ity of military strongholds. After the period of tremendous growth, which peaked in the 2nd century, the cities found themselves in profound crisis in the 3rd to 4th century. The cause of this should be seen in the massive invasions of Germanic tribes, and towards the close of the 4th century also Huns. In the aftermath, the urban and military structures underwent complete transformation, with both ultimately merging into one. This also applied in the case of Novae in Lower Moesia: throughout the latter part of the 3rd, and in the 4th century, the city changed entirely. Novae the castra and the canabae legionis I Italicae, vicus and Municipium Novensium metamorphosed into Civitas Novensis